WEB-BASED EMPLOYEE RECRUITMENT DECISION SUPPORT SYSTEM USING THE FUZZY ANALYTICAL HIERARCHY PROCESS METHOD (CASE STUDY PT. AGROFARM NUSA RAYA) - Setia Mahardika, Vicky Pratama; Sisephaputra, Bonda (Universitas Negeri Surabaya, 2025)
Employees or employees are part the most important thing for the company. So therefore, When recruiting, it must be done carefully maximum in order to obtain quality employees, quality and according to needs. In the process recruitment of new employees, PT. Agrofarm Nusa Raya still using the manual method and not yet apply methods for decision making. A large number of prospective employees make HRD find it difficult to select prospective employees who match the criteria for acceptance in company. To overcome this problem So a Decision Support System is needed web-based by applying the Fuzzy method Analytical Hierarchy Process (Fuzzy AHP). Criteria used for the employee recruitment process namely interviews, psychological tests, Islamic knowledge, work experience, education and certificates. Results The end of the research shows that the application Employee recruitment decision support system can be developed using the Extreme method Programming (XP). In the calculation results applying the Fuzzy AHP method obtained results that the highest score is 1,660 with the name Akbar,while the lowest value is -1.810 with the name Priest. With the existence of a Decision Support System Those who implement Fuzzy AHP will make it easier HRD work in the decision making process related to the final results of employee recruitment.